PISA science framework 2018 vs 2025 and its impact in physics education: Literature review - Utama Alan Deta; Septy Kurrota Ayun; Luthfiyaul Laila; Binar Kurnia Prahani; Nadi Suprapto (Momentum: Physics Education Journal, 2024)
Program for International Student Assessment (PISA) evaluates education systems in participating countries. Junior high school students are tested in math, science, and reading for the PISA Scientific Literacy test. This study contrasts the PISA Science Framework 2018 and 2025. This literature research uses systematic Literature Review (SLR) and bibliometric analysis. The method finds, reviews, evaluates, and interprets all research related to scientific literacy, PISA Framework 2018 and 2025, and its impact on Physics Education. The research used the Scopus database to find PISA Science Framework-related scientific articles. Results showed that PISA Framework 2025 evolves science literacy and scientific information function. The language is simplified to be more coherent by emphasizing the main idea of science. Procedural and epistemic knowledge are expanded and clarified. The finding is also supported by VOSviewer visualization of data results. This framework implies that physics education will assess students' understanding of fundamental physics principles and their rationality in applying them, including decision-making. In conclusion, the PISA Science Framework 2018 needs to be updated to the PISA Framework 2025 by the OECD to accommodate the students' needs in this era.